DEVELOPMENT OF MIDBLOCK CROSSING SAFETY MODEL ON DIVIDED ROAD IN BANDUNG - Dwi Widiawati, Dhiana
Pedestrians are road users who are vulnerable to traffic crashes when crossing the road. The number of pedestrian deaths in Indonesia is 16% due to traffic crashes (WHO, 2018). The fatality rate is quite high, so a study to find out how the safety level are provided for pedestrians, especially when crossing the roads is needed. This study aims to establish safety models which can be used to assess the safety level of crossing, especially on divided roads in Bandung. The crossing locations under study were 30 crossings on divided roads. There are two types of models formed, namely multiple linear regression and ordered probitt. Each model was formed into a major, minor (female and male), and combined models. The models were formed using the pedestrians perception from the results of the rating survey as dependent variable and traffic characteristics, road characteristics, and control characteristics as independent variables. Each model was formed using two types of independent variables. Type 1 is the independent variable with traffic characteristics per type of vehicle, and type 2 is the independent variable with the total traffic characteristics all types of vehicles. Both types of models were formed then compared and the best model selected to assessing the safety level of crossing. The results show that the best model to assess the safety level of crossing is the linear models type 1 (major, female minor, male minor, and combined) as it has lower Akaike Information Criterion (AIC) and Chi Square (X2) values compared to the ordered probit models. From the linear models type 1, it can be concluded that the most influencing parameter which may decrease the safety level of crossing is the absence of zebracross at the crossing location.